A measurement method and device for planar image analysis based on structural illumination features - DING YI; HU QI; HU GUOLIANG; PENG KAI; DENG TIANPING; ZHAN WEIQI; WANG DONGYUN (2021)
The invention provides a measurement method and device for planar image analysis based on structural illumination features, and the method comprises the following steps: projecting stripes to the surface of a to-be-measured object, and obtaining an EPI picture of the to-be-measured object; performing feature extraction on the EPI picture to obtain line segments with obvious linear features; identifying collinear line segments belonging to the same feature point from the line segments with obvious linear features; and determining the coordinates of the three-dimensional scene of the feature point according to the collinear line segment and the relationship among the polar plane position, the straight line slope and the intercept in the EPI image. According to the invention, stripe analysisis carried out on stripe structured light projected to the surface of an object, noise is removed by using filtering and mathematical analysis methods, and an EPI reconstruction result based on structured illumination is opti